CHALLENGES OF CONFLICT OF LAWS IN CYBERSPACE - Said Mabrouki; Naima Akli (International Journal of Innovative Technologies in Social Science, 2026)
The borderless nature of the internet poses significant challenges to jurisdiction and conflict of laws, as traditional territorial legal frameworks struggle to keep pace with the digital age. Although private international law has historically addressed cross border disputes, its rules have not evolved at the speed of technological change. In response, legal scholars advocate for a unified global framework often referred to as Lex Electronica enforced by digital judicial bodies. They argue that the internet’s erosion of national boundaries necessitates new models of governance.Nevertheless, private international law remains essential in practice, offering adaptable mechanisms such as tort liability principles for regulating online behavior. To effectively navigate the legal complexities of globalization, existing legal frameworks must be recalibrated, and national laws must evolve to reflect digital realities. At the same time, emerging actors like ICANN challenge traditional notions of sovereignty, exerting regulatory influence over cyberspace and raising critical questions about the capacity of legal systems to balance innovation with accountability.